Long-term effects of orchiopexy and orchiectomy on the testes of rats with testicular torsion. Issue 3 (June 2022) - Tasci, Aytac; Uguralp, Sema; Akatli, Ayse Nur; Arslan, Ahmet Kadir; Karabulut, Aysun Bay
Summary: Introduction: Ischemia/reperfusion injury occurs after testicular torsion, levels of free oxygen radicals and inflammatory cytokines are increased in both the torsional and contralateral testis, leading to testicular injury. Objective: The present study investigated whether orchiopexy or orchiectomy after testicular torsion was superior in terms of fertility potential in the long term. Study design: Following 720°, 4 h left testicular torsion, orchiectomy or orchiopexy was performed on 84 rats, which were then sacrificed and evaluated for testicular function at day 1, at 3 months and 6 months (n = 14 per group). An additional 14 rats were in the control group. Results: Follicle stimulating hormone (FSH), luteinizing hormone (LH), and testosterone levels were significantly lower in the orchiopexy group than the orchiectomy and control groups after 3 months. However, there were no significant differences in hormone parameters among the three groups after 6 months. The hormone levels, Johnsen score, seminiferous tubule diameter, and inducible nitric oxide synthase (iNOS) expression at 3 and 6 months were not significantly different between the orchiectomy group and controls. Histopathological analyses at 3 and 6 months indicated significant decreases in Johnsen score and seminiferous tubule diameter in the ipsilateral testis in the orchiopexy group. At 3 months, the level of iNOS expression in the contralateral testis was significantly lower in the orchiopexy group than in other groups. At 6 months, however, it was not significantly different between the orchiopexy and control groups. There were no significant differences in iNOS expression at 3 or 6 months in the orchiectomy group compared to controls. Discussion: The ipsilateral testis in the orchiopexy group began to atrophy at 3 months, and the degree of atrophy became more evident at 6 months. The level of iNOS expression was low in the bilateral testis at 3 months in the orchiopexy group, and sperm in the contralateral testis were not yet functionally healthy. The level of iNOS expression in the ipsilateral testis decreased further at 6 months in the orchiopexy group, while that in the contralateral testis returned to the normal level. Conclusion: Testicular functions were restored faster after orchiectomy compared to orchiopexy following testicular torsion. However, follow-up of the rats for 6 months demonstrated that orchiopexy or orchiectomy procedures conducted on the testicular torsion had no effect on future fertility potential after 4 h of torsion.